Headdress: Faith and practice in everyday life in Buddhism (The case of the temple of the tooth Buddhist religious activities and the cultural headdress of Sri Lanka) - G. M. RANATHUNGA; P. V. M. KARUNARATHNE; S. S. V. DE SILVA (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: Clothes are more than just a means of keeping warm; they also convey meanings about the social and cultural norms to which they belong. Since ancient times, Sri Lankans have dressed in accordance with cultural norms and traditions for Buddhist religious ceremonies. Located in Kandy, a city recognised by UNESCO as a World Heritage Site, the Temple of the Tooth is the subject of this investigation into a particular type of musician’s headdress.Method: The study is ethnographic in nature, with the participation of observers serving as its conceptual foundation. Scholars attended rituals held at the Temple of the Tooth, conducted interviews with musicians who performed there and analysed the results.Findings: This vital piece of the headdress has been worn in a specific manner since ancient times. The headdress can convey various meanings, including the importance of the occasion, the wearer’s glitzy personality, the depth of their hospitality, the respect they have for the Buddha, and their level of artistic skill.Implications/Novel Contribution: This study summarises the significance of the turban in Sri Lankan culture. The research familiarises the world with Sri Lankan culture.